Impact of partial encapsulation on the fire dynamics of an open‐plan compartment with exposed timber ceiling and columns: CodeRed #04. (21st January 2023) - Kotsovinos, Panagiotis; Christensen, Eirik G.; Glew, Adam; O'Loughlin, Eoin; Mitchell, Harry; Amin, Rikesh; Robert, Fabienne; Heidari, Mohammad; Barber, David; Rein, Guillermo; Schulz, Judith
Abstract: The use of mass timber in construction is becoming a compelling option when faced with the high carbon footprint of traditional concrete and steel production. However, fire safety standards are yet to evolve to support these designs. Encapsulation is commonly used to protect all, or some, of the timber surfaces and reduce the risks introduced. This paper presents the results from CodeRed #04, the final experiment of the CodeRed experimental campaign. This experiment was carried out inside a purpose‐built facility to capture fire dynamics in large compartments with exposed timber. CodeRed #04 had identical characteristics to CodeRed #01 with the exception that 50% of the cross‐laminated timber (CLT) ceiling was encapsulated. The experiments were intentionally similar to the traveling fire experiments, x‐ONE and x‐TWO, which had a non‐combustible ceiling to enable a direct comparison. The overall fire dynamics experienced in CodeRed #04, intersect the characteristics observed in CodeRed #01 and x‐ONE and x‐TWO.1 . In CodeRed #04, there was a delay in the ignition of the CLT ceiling as the CLT directly above the crib was encapsulated. Once the CLT ceiling ignited, the fire spread rapidly throughout the compartment. The peak heat release rate (HRR) was estimated to be approximately 100 MW, a 17% decrease from CodeRed #01 . Following CLT ignition the resulting fire duration, maximum temperatures, and heat fluxes were broadly similar to CodeRed #01 . Flame heights of approximately 1.5 m were observed from the windows while flame heights of 2.5–3 m were observed in CodeRed #01 . Therefore, flame heights were found to be comparable to x‐TWO.1, though over a greater number of windows, reflecting the greater extent of simultaneous burning within the compartment. The average charring depth of the exposed CLT panels was 25 mm, which is similar to that measured in CodeRed #01 ‐suggesting that the fire severity near the ceiling was not strongly impacted by the 50% encapsulation of timber. No charring was observed where the ceiling was encapsulated and loaded service fixings installed through the encapsulation were found to be less likely to fail than when attached directly to the exposed timber. Smoldering was observed after the cessation of flaming and, in a few locations, was observed to progress through the thickness of the CLT panel and continue behind the encapsulation. This illustrates that, while encapsulation can succcessfully prevent flaming, it cannot be completely relied on to avoid smouldering. The findings from CodeRed #04 contribute to the development of evidence‐based fire safety design methodologies for exposed mass timber buildings.